PENERAPAN KOMUNIKASI PEMASARAN TERPADU DALAM MENINGKATKAN KEGIATAN PEMASARAN DI TEMBI RUMAH BUDAYA YOGYAKARTA - , DZIKRINA NOOR F; , Arina Pramusita SIP., M.Si ([Yogyakarta] : Universitas Gadjah Mada, 2014)
The research aims to know about the implementation of integrated marketing communication in enhancing marketing activities and obstacles faced in Tembi Rumah Budayain carrying out its integrated marketing communication strategy. The research conducted in Tembi Rumah Budaya. Data collected through interview, observation and literature study. The research methods used were descriptive research methods by primary and secondary dataThe research methods used were descriptive research methods by primary and secondary data. The result were, Tembi Rumah Budaya has implemented integrated marketing communication strategy and combined eight element of marketing communication mix. Obstacles encountered were The delivery of a message was not efficient, a lack of marketing staff, a competitor around, the economic crisis,and the condition of the surrounding environment that is less support.